DISTRIBUTION OF LEACHED WATER PENETRATION INTO GROUND-WATER AT PUBLIC WELLS AROUND THE END POINT LAND-FILL AREA (CASE STUDY OF TPA LEUWI GAJAH-BANDUNG) - Wagiono - (Bionatura, 2003)
The objective of the research was to find out the distribution of leached waterpenetration into groundwater. The research was carried out from April to June2001. Hydrochemical, Meteoric, and 18Oxygen content methods were used formeasuring the distribution of leached water penetration. The result indicatedthat the leached water distribution at public wells around The end point landfillarea of Leuwi Gajah reached up to one kilometer from outside border on southwestdirection following stream flow of small river of Cirendeu; while on otherdirections there were no indication of leached water penetration to public wells.